2019
DOI: 10.1080/22797254.2019.1580538
|View full text |Cite
|
Sign up to set email alerts
|

Forest management and sustainable urban development in the Curonian Spit

Abstract: A major challenge in forest management is to balance the competing interests of different users. The conservation of biological diversity is an important goal when managing forests in an ecologically sustainable way, but this overlooks aspects of sustainability in terms of urban development and other land use. This research examines physical and biological processes leading to changes in the spatial and temporal land cover on the Curonian Spit, in Lithuania, pre-and post-1990 when the political situation chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In that case, however, the researcher encounters the problem of having to establish the criteria for classifying land use for space images by himself. In this case, quite complex supervised classification methods are employed (Galinienė et al 2019;Bagdanavičiūtė et al 2018;Estima, Painho 2019;Hütt et al 2016;Kafi et al 2014). The use of supervised and unsupervised space-based methods for land cover mapping has shown that unsupervised (free) classification is not suitable for data acquisition and further use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, however, the researcher encounters the problem of having to establish the criteria for classifying land use for space images by himself. In this case, quite complex supervised classification methods are employed (Galinienė et al 2019;Bagdanavičiūtė et al 2018;Estima, Painho 2019;Hütt et al 2016;Kafi et al 2014). The use of supervised and unsupervised space-based methods for land cover mapping has shown that unsupervised (free) classification is not suitable for data acquisition and further use.…”
Section: Discussionmentioning
confidence: 99%
“…The use of supervised and unsupervised space-based methods for land cover mapping has shown that unsupervised (free) classification is not suitable for data acquisition and further use. The supervised classification provides more accurate interpretative data that can be used in further studies, e.g., for assessing the spatial distribution of land cover for the analysis of geodynamic processes (Galinienė et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Land cover data (1990, 2000, 2010 and 2020) by the Director Generals of Planning and Environmental Management, Ministry of Environment and Forestry, Indonesia were overlaid with administrative data from the Geospatial Information Agency use Geographic Information Systems (GIS) approach. This approach is a tool for detecting land use change, deforestation, monitoring, planning, and forest management [14]. The land cover is then used in conducting forest and non-forest analysis which refers to the land cover class issued through the Regulations of the Director General of Forestry Planning number P.1 / VII-IPSDH / 2015 concerning Procedures for Monitoring Land Cover and is based on SNI 7645-2010.…”
Section: The Forest and Non-forest Analysismentioning
confidence: 99%
“…,929.59 ha in 2020. Land cover data from the Ministry of Environment and Forestry of the Republic of Indonesia uses Landsat imagery, namely multi-time spatial analysis using Landsat imagery combined with GIS gives good and efficient results[20,14]. The highest percentage of initial forest area (>50%) can be seen in table 2.…”
mentioning
confidence: 99%
“…Some researchers report about the gradually deteriorating conditions for vegetation survival on the Curonian Spit coastal sand dunes during the last years [6]. The others state about favorable conditions for forest cover expansion in Curonian Spit: there was a decrease in forest cover during 1989-2008 period, however 1% annual increase of forest cover is observed since 2009 [7]. These local processes forming dunes landscape may induce equilibrium between areas with active eolian processes and areas covered by herbaceous vegetation or artificial cover.…”
Section: Introductionmentioning
confidence: 99%